The History of International Cooperation and Integrations in East Central Europe - Lysý, Miroslav (Lectures on East Central European Legal History, 2022)
This chapter is concerned with the development of international relations, international cooperation, and international law in Central Europe from the beginning of the Middle Ages up until present times. The topic encompasses the relationship between international and constitutional law. While the first centuries of the Middle Ages can be characterized as a struggle between imperial universalism (the Frankish empire and the German–Roman empire), beginning in the 12th century, it was the particularism of Central European countries like Poland and Hungary (and particularism within the German–Roman empire) that set the pace. Various particular units, however, often integrated into larger unions, united as personal or (later) real unions. In the case of Hungary and the Czech lands, the idea of Crown lands was created in order to express unity among various countries with different levels of integration. Among many unions, the Habsburg empire proved to be very successful and viable and led many unification attempts toward the Austrian–Hungarian Compromise of 1867. Dualistic statehood lasted for half a century, and after the First World War, it was replaced by a newly organized Central Europe, with new states, new borders, and a new system of international security. Versailles peace, however, resulted in new controversies and new hostile relations in the late 1930s. After Anschluß of Austria and especially the Munich Treaty (1938), the Versailles system in Central Europe was definitively gone. A new order was set after the end of the Second World War, when Central Europe became part of the Soviet bloc. This lasted until 1989, when the Soviet-controlled regimes in Central Europe ceased to exist and Central Europe started to integrate with structures of the European Union and the North Atlantic Treaty Organization. KEYWORDS: history of Central Europe, integration, personal union, real union, dynasty policy, peace treaties, Versailles peace system, Munich Treaty.